A Municipal Register of the City of Concord, Containing the City Charter and Ordinances, the Rules of the City Council, and a List of the City Officers Page 39, Image 40 (1857) - (:unkn) unknown (General Publisher, 1853)
Prohibited the discharge of firearms in the city on the first day of the week
--
Keywords: DISCHARGE